Transient expression of genes introduced into cultured cells of Drosophila. - Di Nocera, P P (1983)
Recombinant plasmids in which the sequence encoding the bacterial chloramphenicol acetyltransferase (CAT; acetyl-CoA:chloramphenicol 3-O-acetyltransferase, EC 2.3.1.28) has been placed under the control of Drosophila heat shock protein 70 (hsp 70) or copia promoters have been introduced into cultured cells of two Drosophila species (Schneider II line of Drosophila melanogaster and D. immigrans) as calcium-phosphate complexes. Within 1-2 days after transfection functional CAT enzyme was detected in cells exposed to either CAT recombinant. The expression of the bacterial information depends on the activity of the Drosophila promoters because plasmids in which the Drosophila DNA fragments were fused to the CAT coding sequence in inverted orientation did not support the synthesis of CAT enzyme activity. Low levels of CAT activity and of hybrid mRNA were detected in cells transformed with hsp-cat recombinants when the cells were maintained at room temperature, and both mRNA levels and CAT activity increased substantially after a brief exposure to 37 degrees C. hsp-cat mRNA has the same 5' terminus as authentic Drosophila hsp 70 messenger. These experiments document a practical system for the introduction and expression of isolated genes in cultured cells of Drosophila.